2021
DOI: 10.12788/jhm.3621
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Hospitalist Care in Asia: Experiences From Singapore, Taiwan, Korea, and Japan

Abstract: ince its inception in the mid-1990s, the hospitalist model of care has enjoyed robust growth in the United States, increasing to around 20,000 providers by the end of its first decade. 1,2 Since then, it has far outstripped early predictions of adoption, currently standing at more than 50,000 hospitalist providers. 2 Although driven by numerous factors, including system-based management needs, provision of inpatient care for unassigned patients, and demands for improved patient safety and satisfaction, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…30 These Asian countries and Japan have the same issues regarding medical quality and patient safety. 10 In this study, we revealed the exact effects of the reduction of LOS.…”
Section: Impact On Losmentioning
confidence: 84%
See 2 more Smart Citations
“…30 These Asian countries and Japan have the same issues regarding medical quality and patient safety. 10 In this study, we revealed the exact effects of the reduction of LOS.…”
Section: Impact On Losmentioning
confidence: 84%
“…7 Currently, HS have spread to other countries from the USA and have reached East Asian countries, including Singapore, Korea and Taiwan, which have demonstrated notable improvements in the quality of care. [8][9][10] For example, Korea introduced a HS into general medicine and surgery in 2016 to solve their problems such as patient safety, healthcare quality and residents' well-being. 11 12 The HS improved many clinically significant indicators about not only medical quality and safety but also patient satisfaction.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the presence of hospitalists in Japan has shortened hospital stays and reduced costs for common diseases such as pneumonia and heart failure [24][25][26]. Similarly, a report summarising the role of hospitalists in four Asian countries also emphasizes the importance of their role in addressing healthcare quality [5]. The results of these previous studies indicate that quality and safety of medical care is a core interest for Japanese hospitalists and that their work is improving patient care in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, the number of hospitalists has continued to grow, with current estimates of at least 44,000 adult hospitalists in the United States of America (USA) [3]. An interesting aspect of the rapid expansion of hospital medicine is the growth of the eld beyond the USA including Asian Countries [4,5,6]. While some of the reasons for the development of hospital medicine internationally are the same as in the United States, there are differences in training, health care systems, regulations, and cultural norms underscoring the practice of hospital medicine in different countries.…”
Section: Introductionmentioning
confidence: 99%